Kulturna politika Karla Velikega in srednjeveška latinska književnost - Malmenvall, Simon (Primerjalna književnost, 2016)
This article presents the key characteristics of the cultural policy of the king and emperor Charlemagne (768-814), focusing mainly on the ideational presuppositions of literary production in Latin during the Carolingian Renaissance from the end of the eighth century to the end of the ninth century. The author suggests that, as a motivation to adjust the authority of the classical Latin style to the Christian worldview, the creators of the Latin literature of the time formed a special notion about the continuity of the Roman world, which can be captured by the concept of Roman-ness (or Romanitas). At the same time, this notion of continuity gave sense to Charlemagne's overall aspirations to build a new (western) Roman Empire.
Keywords: Carolus Magnus, frankovski kralj, 742-814; latinska književnost; Middle Ages; srednji vek; karolinška renesansa; kulturna politika; krščanstvo; Christianity; rimstvo